A novel variant of PLA2G6 gene related early-onset parkinsonism: a case report and literature review - Cai, Dapeng; Wu, Haohao; Huang, Baogang; Xiao, Weiwei; Du, Kang (Frontiers in Neurology, 2024)
This study reported a case of early-onset parkinsonism associated with a novel variant of PLA2G6 gene. The boy started at the age of 11, with gait instability and frequent wrestling as the initial symptoms. With the disease progression, his gait instability gradually increased, and dysphagia and dysarthria occurred, without obvious cognitive decline. The head MRI showed that the cerebellum was obviously atrophied. The initial diagnosis of the boy was early-onset parkinsonism, Hoehn-Yahr grade was 5. The patient's whole genome sequencing indicated that the compound heterozygous variation of PLA2G6 gene was c.1454G>A (p.Gly485Glu)/C.991G>T (p.Asp331Tyr). Pedigree analysis showed that the younger brother carried the same variant with mildly clinical symptoms. His normal mother was the carrier of the c.991G>T variant. This study also reviewed 62 unrelated families of PLA2G6 gene related early-onset parkinsonism reported. The results showed that the proportion of female probands was higher, and the mean age of onset was about 23.0 years old. The initial symptoms were mainly bradykinesia and psychosis, and the onset of tremor was relatively rare. Cerebellar atrophy occurred in 41 patients (66.1%). Among the reported mutations, the most common mutation was c.991G>T with 21 families (33.9%), followed by c.2222G>A with 8 families (12.9%), other mutations were rare. The c.991G>T mutation only appeared in Chinese families, and it was a hot spot mutation in Chinese. The initial symptoms of patients with different mutations were quite heterogeneous.